Effectiveness of the 112 Call Center Service at the Department of Communication and Informatics in Samarinda City - Anisa Dea Syafira; Cathas Teguh Prakoso (Dinasti Publisher, 2024)
Public service continues to be a significant element in developing countries to meet the needs of the community. The Samarinda City Government has introduced an innovative public service, the 112 Call Center. This study aimed to determine the effectiveness of the 112 Call Center service in Samarinda City. The method used in this research is a qualitative approach. The research results show that the effectiveness of the 112 Call Center service at the Department of Communication and Informatics in Samarinda City is quite substantial as this service has proven beneficial in supporting security and handling emergency situations faced by residents. This service allows people to quickly contact the authorities when emergency situations occur, such as traffic accidents, fires, crimes, and other emergencies.